(untitled) (Research, Society and Development, 2021)
This study aimed to evaluate behaviors associated with handling of sanitizers in a largely low-income neighborhood located in Itu – SP, Brazil. This work was carried out based upon application of a semi-structured, individual and closed questionnaire to 100 inhabitants of Parque São Camilo aged 30 or older. The extent of the associations between the assessed factors was determined by Fisher exact and these were considered significant when p<0.05. Disinfecting products and fabric softeners were the sanitizing agents most often used by the population. Regardless of age, sex, previous history of intoxications and use of personal protective equipment, the habit of reading product labels was associated with handwashing and not using clandestine products. It can be inferred that either public policies aimed at conscientizing the local population or their literacy might be the reason for the assessed population having safe sanitizer handling habits and not using clandestine products.